Implementation of a standardised questionnaire for documenting preoperative respiratory illness in paediatric patients - Abby Victoria Winterberg; Stacie Richmond; Nathaniel T G Tighe; Jennifer Buckley; David Winthrop Buck (BMJ Open Quality)
Paediatric patients often present with symptoms of respiratory illnesses in the weeks leading up to surgery. Current or recent illness can increase the risk of experiencing perioperative respiratory complications. Ideally, children with recent illnesses should be identified before coming to the hospital to determine the safest course of action. We recognised that our system lacked a standardised process for documenting preoperative respiratory illness during the preoperative phone call. The global aim of this quality improvement initiative was to decrease paediatric perioperative respiratory adverse events. The SMART Aim (Specific, Measurable, Achievable, Relevant and Time-bound) was to increase the percentage of patients with standardised documentation of preoperative respiratory illness from 0% to 90% by 1 March 2023. Implementation of a standardised preoperative illness questionnaire increased standardised illness documentation from 0% to 95%. Nurses quickly adopted this intervention and easily integrated it into their routine workflow. Clinical leaders elected to implement the intervention electronically across all three operating room (OR) locations (main OR, satellite location and procedure centre). Future implementation of additional standardised preoperative processes will be needed to improve the global aim of decreasing perioperative respiratory complications.